How Types of Organisational Culture Shapes Successful Start-ups within Malaysia - Kuah, Shen Yang (2016)
Start-ups is the new wave of firms which are now mushrooming around Malaysia. However, as this wave is still at its infancy the success rate of start-ups in Malaysia is extremely low. It has been long established that organisational culture does indeed effect the performance of a firm, however there haven’t been any reports on the effect of organisational culture on the success of start-ups. The objective of this report is to investigate how different types of organisational cultures contribute to the success of start-ups in Malaysia. In order to do that,this research has decided to use a quantitative approach through the usage of a questionnaire to acquire the all relevant data. 80 requests were send out but there were only 43 respondents. This report has successfully revealed the different existing organisational culture types in current firms and also identified the main organisational culture types existing within each participating start-ups. After which the report successfully examine the effects of the organisational cultures to the corresponding start-ups. The conclusion obtained from this report is that firstly, organisational culture does effect the success of the start-ups in Malaysia. Second, contrary to what was concluded in the literature, both bureaucratic and competitive culture was proven to have a positive effect on the success of start-ups in Malaysia. Third, as the literature suggested, the participative and learning culture was also proven to have a positive effect on the success of start-ups in Malaysia. Forth, the ranking for organisational culture based on the degree of positive effect on the success of start-ups starting from most effective: learning culture, participative culture, competitive culture, and lastly bureaucratic culture.